Pajak Kendaraan Bermotor : Persepsi Wajib Pajak terhadap Pelayanan di SAMSAT Kabupaten Serang - Adella Maharani; Munawaroh Munawaroh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Tax is a source of regional income which has an important role in the development of infrastructure and public services. However, the effectiveness of tax compliance is often influenced by various factors, including public perception of services in the motor vehicle tax payment process, which is often considered complicated and confusing. This article aims to provide an overview of taxpayers' perceptions of motor vehicle tax services at the Serang Regency Samsat. This research used a quantitative approach involving 68 respondents who were taxpayers in the Serang Regency Samsat. The methods applied in this research include descriptive statistical analysis, correlation tests, and linear regression.